Imperatives for Curbing the Growing Violence against Women and Girls in Nigeria: Options Beyond Legislation, Sympathy and Public Condemnation - Manjo, Yusuf Garba (Universitas Islam Bunga Bangsa Cirebon, 2025)
Violence against women and girls in Nigeria has reached disturbing proportions, manifesting in various forms such as domestic abuse, rape, sexual harassment, forced marriages, and other harmful practices. This increasing scourge of physical violence and killings of women and girls for money-making rituals has further destabilised the lopsided gender balance in Nigeria, with the female gender being the most extraordinary sole victim. Violence against women and girls in Nigeria has become a serious contemporary problem that has to be addressed. Nigerian must create a new culture where women and girls are secured and valued by interrogating the underlying causes of violence, identifying its terrible impact on victims, and proffering preventive measures beyond legislations and public condemnations as well as, examine the existing legal frameworks that is targeted solely on meted minimum punishment on offenders, with no provision for compensation for the victims. Despite existing legal frameworks, public advocacy, and widespread media condemnation, the prevalence of gender-based violence continues to rise, revealing significant gaps in the effectiveness of current interventions. This study explores the imperatives of curbing the growing incidence of violence against women and girls in Nigeria by examining options that go beyond laws, sympathy, and media outrage. The study employs a qualitative approach, drawing insights from existing literature and policy reports to identify structural, cultural, and socio-economic drivers of violence against women and girls. The study finds that while legal instruments are necessary, they are insufficient in isolation from other measures. Therefore, sustainable solutions must include community-based education, empowerment programs for women, reform of traditional and religious institutions, rehabilitation of perpetrators, and the transformation of societal norms that normalise violence. The study concludes that a multidimensional, preventive, and participatory approach is essential to effectively curb the growing menace of violence against women and girls in Nigeria.